The Incubation and Business Development Program for Students of University of North Sumatra (USU) - Buchari; Hutagalung, Arief Qaedy; Sitompul, Dany Perdana; Dribawanto, Nana Dyki (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Business Incubation and Development Program for USU Students aims to create new independent entrepreneurs based on science and technology, enhance the network between university entrepreneurship and the community, industry, and other institutions, and establish a suitable entrepreneurial guidance model for PMW/P2MW students, those initiating business ventures. This program is slated to run for 3 (three) years, from 2023 to 2025. In its inaugural year, it will nurture 20 (twenty) tenants, consisting of 1 (one) P2MW student and 19 (nineteen) PMW students forming 18 groups who are venturing into new businesses. The program begins with the Pre-Immersion Phase, involving the recruitment process for participants (tenants), followed by training encompassing 3 (three) stages: Product Design Training, Creativity and Business Innovation Training, Design Thinking and Business Model Training. Subsequently, participants undergo the Immersion Phase, engaging in internships at SMEs, followed by the Post-Immersion Phase involving business coaching, mentoring, business gatherings, curation, demo day, pitching, and concluding with program monitoring and evaluation. The output of this KBM program aims to generate 5 (five) new student entrepreneurs.